Implementation of a Teaching Electronic Medical Record within Didactic Instruction Using a Drug Information Question Assignment - Jacqueline Wasynczuk; Amy H. Sheehan (MDPI AG, 2021)
Background: Pharmacy graduates are expected to be practice-ready to deliver quality patient care, which includes having comprehensive knowledge of health informatics and electronic medical records (EMRs). The purpose of this study was to (1) incorporate an EMR within a pharmacy student assignment, and (2) assess student perceptions of use of the EMR. Methods: Student pharmacists received a patient-specific drug-related question and were required to use an EMR to provide an accurate response. Following completion of the assignment, students were invited to complete a retrospective, pre-post survey instrument to collect their perceptions. Results: Only 28.8% of respondents reported prior experience using an EMR. Student perceptions about use of an EMR within the didactic setting significantly improved from before to after the assignment. Differences were found in respondents who agreed that didactic use of an EMR increased their confidence in obtaining information from an EMR (20.5% to 82.8%) and improved their knowledge of EMR systems (61.4% to 89.3%). Conclusions: Implementation of an EMR within didactic instruction may serve as the first exposure to health informatics for students and positively impacts student perceptions of these tools prior to entry into pharmacy practice.